The over-cascading system of cadre evaluation and China's authoritarian resilience. (March 2021) - Qi, Rui; Shi, Chenchen; Wang, Mark
China's cadre evaluation system – the personnel management system used to assess the performance of government officials in the party-state – is considered an important tool for upper-level governments to supervise and regulate lower-level agents. This system is one of the key factors contributing to the Chinese Communist Party's (CCP) authoritarian resilience. Deficiencies of this system are exemplified by the 'blind pursuit of GDP', selective implementation, gaming, collusion, and data fabrication. The CCP has been reforming this system to strengthen its monitoring and political control over local government cadres, especially at the county level, and it is a crucial component in the step-by-step hierarchical power structure. While current literature focuses largely on the assessment content of such reform, this article pays specific attention to the changes in the cascading evaluation structure of province to prefecture to county. The article identifies a new dynamic of 'over-cascading' whereby provincial governments bypass prefectural governments and directly evaluate county officials, resulting in the co-existence of prefecture-county and province-county evaluations. This article also explores the functioning mechanism of this dual structure and argues that this structural change in the cadre evaluation system is breaking the traditional hierarchical governance structure and enhancing authoritarian resilience of the CCP because it provides a new route for over-cascading governance between provincial and county governments. This research contributes to the conceptualization of the over-cascading governing structure of the CCP and fills gaps in the literature on structural changes in China's cadre evaluation system.